The culmination of multidrug-resistant efflux pumps vs. meager antibiotic arsenal era: Urgent need for an improved new generation of EPIs - Chetri, Shiela (Frontiers in Microbiology, 2023)
Efflux pumps function as an advanced defence system against antimicrobials by reducing the concentration of drugs inside the bacteria and extruding outside. Various extraneous substances, including antimicrobials, toxic heavy metals, dyes, detergents etc., are removed by this protective barrier composed of a sequence of transporter proteins found in between cell membrane and the periplasm within bacterial cell. In this review, multiple efflux pump families are analytically and expansively summarized and their potential applications are thoroughly discussed. Additionally, this review also discusses a variety of biological functions of efflux pumps, comprising their role in the formation of biofilms, quorum-sensing, their survivability and the virulence in bacteria as well as the genes/proteins associated with efflux pumps have also been explored for their potential relevance to antimicrobial resistance and antibiotic residue detection. A final discussion centres around efflux pump inhibitors, particularly those derived from plants.